Comparisons of Health Education, Group Medical Care, and Collaborative Health Care for Controlling Diabetes - Mehl-Madrona, Lewis (The Permanente Journal, 2010)
Introduction: This article presents early-phase clinical investigations into how to care for people with diabetes mellitus (DM) in an outpatient setting, focusing on efforts at improving care for Native Americans using conventional and nonconventional interventions—in particular, whether engaging people with DM using culturally specific and spiritual methods were more effective in reaching several DM management goals than conventional methods alone. This outreach may be seen as an example of delivering culturally competent medical care, a prime objective of family medicine. Methods: In a three-year, serial process, three interventions included: diabetic health education, group medical care for diabetes, and shared collaborative care, which included medical, psychological, and spiritual care provided simultaneously. Results: In all clinical outcome data—multiple measures of glucose control—statistically significant differences were found between shared, collaborative care and group medical care, and also between these and standard health education and conventional care. Discussion: Several potential explanations are offered, with discussion, for how shared, collaborative care can be more helpful than group care or individualized care alone, including: stress reduction, increased social support, producing more positive health beliefs, and acting as a kind of naturalistic biofeedback.